The Analysis of Perceived Organizational Support and Self Efficacy as Important Factors in Improving Employee Performance - Decinta Najlaputri; Ratri Wahyuningtyas (Cita Konsultindo Research Center, 2024)
Currently, the world is undergoing significant changes, particularly in the economic sector. The competition among companies is escalating in this era of globalization. One of the frequently encountered issues is the adverse impact of resource mismanagement by companies, which can affect the performance outcomes of employees. The aim of this research is to analyze the importance of Perceived Organizational Support and Self Efficacy in enhancing Employee Performance at PT. Enerco RPO Internasional. The research employs a descriptive analysis method, targeting the employee population of PT. Enerco RPO Internasional. The sample consists of 73 respondents selected through simple random sampling. Data is collected through the distribution of questionnaires to the employees of PT. Enerco RPO Internasional. Based on the research findings, the author suggests that PT. Enerco RPO Internasional should consistently maintain and enhance Perceived Organizational Support and Self Efficacy to optimize the resulting performance.